The present - Gill, Bob, 1931-2021. (San Francisco, Calif. : Chronicle ; Grantham : GBS [distributor], 2010)
A young boy imagines all the things that can be inside a present he found in his parent's closet, and after a visitor arrives, he realizes sharing is the best gift of all.
Keywords: Generosity -- Juvenile fiction; Gifts -- Juvenile fiction; Children's stories; Generosity -- Fiction; Birthdays -- Fiction; Gifts -- Fiction; Generosity -- Fiction; Birthdays -- Fiction; Gifts -- Fiction